Frequency of oncologic emergencies in children with newly diagnosed cancer at the Vietnam National Children Hospital - Lan, Bui Ngoc; Tinh, Nguyen Thi; An, Vu Van; Tuyet, Nguyen Thu; Khoi, Nguyen Ngoc; Agrawal, Anurag K.; Michelle, Hermiston L.; Dung, Le Thi Thuy (Tạp chí Nghiên cứu Y học, 2025)
Oncologic emergencies are life-threatening complications that require urgent recognition and management in pediatric cancer patients. This study aimed to evaluate the pattern of oncologic emergencies as well as its frequency in newly diagnosed childhood cancers at Vietnam National Children’s Hospital (VNCH). From July 2019 to June 2020, 392 children aged 0 - 15 years were newly diagnosed with cancer. The median age was 3 years old, and males accounted for 58% of cases. The most common forms of cancers were acute leukemia (37.8%), neuroblastoma (19.4%), lymphoma (11.5%), and malignant brain tumors (9.9%). Oncologic emergencies were present in 19.4% of patients at diagnosis, with hematological emergencies such as severe anemia (25%) and thrombocytopenia (26%) being the most frequent, followed by respiratory failure (17%) and leukocytosis (11%). Mortality within 7 days due to oncologic emergencies was 7.9%, primarily caused by superior vena cava syndrome and tumor lysis syndrome. These findings emphasize the need for early detection and timely management of oncologic emergencies to improve treatment outcomes in pediatric cancer patients in Vietnam.